Estado actual del mejoramiento por arquitectura en el frijol arbustivo - Gutiérrez, J.A. (International Center for Tropical Agriculture, 1980)
Towards the end of 1977, the Bush Bean Architectural Improvement Project at CIAT was started with the following objectives: (1) to reduce yield differences between small- and large-seeded types; (2) increase yield capacity and (3) make the crop more attractive and competitive for the different production systems. The pedigree and the fast, intermating and selection (FIS) methods are being used. Early generations (F4) are used for character recombinations. From previous crossings, 36 lines were selected; those of type III had reclining stems and branches and, therefore, their pods had little contact with the soil; and those of type 11, a strong stem and retarded senescence. Eighteen lines of habit 11 were produced with a strong, erect stem. In 1978, parents were used for more specific architectural components. It is necessary to intensify the improvement of types II and III. (CIAT)